Diversity of Cichlid Fishes (Cichliformes: Cichlidae) in Chiapas, Mexico: A practical identification key with updated distribution maps - Gómez-Martínez, Roni Fernando; López-Vila, Jesús Manuel; Matamoros, Wilfredo A.; González-Díaz, Alfonso A.; Gómez-González, Adán Enrique (Zootaxa, 2022)
To accurately identify the species that make up the assemblage of the family Cichlidae in the Mexican state of Chiapas, we first updated the total species account (36 species) for the state and then created an identification key. For the distribution maps, the geographic records were projected using a geographic information system considering the layers of the two largest basins in the state (Grijalva and Usumacinta) and the Chiapas coast basin. The dichotomous key includes meristic, morphometric and coloration patterns that facilitate species identification present in the state. Rheoheros coeruleus (Stawikowski and Werner 1987) and Vieja breidohri Werner and Stawikowski 1987 are included in a key for the first time. The distributions of Paraneetroplus gibbiceps Steindachner 1864a, Rheoheros coeruleus, and Vieja zonata Meek 1905 in the state are mapped for the first time, and the range of 16 species was expanded. By updating and creating tools of great taxonomic use, we contribute to the study of this complex family with high morphological diversity.